Inflammatory Indexes for Assessing the Severity and Disease Progression of Ulcerative Colitis: A Single-Center Retrospective Study - Lin, Hanyang; Bai, Zhaohui; Wu, Qiong; Chu, Guiyang; Zhang, Yongguo; Guo, Xiaozhong; Qi, Xingshun (Frontiers in Public Health, 2022)
Background: Active and severe ulcerative colitis (UC) and non-response to 5-aminosalicylic acid (5-ASA) are related to poor outcome, and should be accurately identified. Several integrated inflammatory indexes are potentially useful to assess the disease severity in patients with acute or critical diseases, but are underexplored in UC patients. Methods: UC patients consecutively admitted to our hospital between January 2015 and December 2020 were retrospectively grouped according to the activity and severity of UC and response to 5-ASA. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), neutrophil-to-platelet ratio (NPR), platelet-to-albumin ratio (PAR), C-reactive protein-to-albumin ratio (CAR), and C-reactive protein-to-lymphocyte ratio (CLR) were calculated. Areas under receiver operating characteristic curves (AUC) were calculated. Results: Overall, 187 UC patients were included, of whom 151 were active, 55 were severe, and 14 were unresponsive to 5-ASA. Active UC group had significantly higher NLR, PLR, SII, and PAR levels. SII had the greatest predictive accuracy for active UC, followed by PLR, PAR, and NLR (AUC=0.647, 0.641, 0.634, and 0.626). Severe UC group had significantly higher NLR, PLR, SII, PAR, CAR, and CLR levels. CLR had the greatest predictive accuracy for severe UC, followed by CAR, PLR, SII, NLR, and PAR (AUC=0.732, 0.714, 0.693, 0.669, 0.646, and 0.63). Non-response to 5-ASA group had significantly higher CAR and CLR levels. CAR had a greater predictive accuracy for non-response to 5-ASA than CLR (AUC=0.781 and 0.759). Conclusion: SII, CLR, and CAR may be useful for assessing the severity and progression of UC, but remain not optimal.